EAES recommendations for recovery plan in minimally invasive surgery amid COVID-19 pandemic - Arezzo, Alberto; Francis, Nader; Mintz, Yoav; Adamina, Michel; Antoniou, Stavros A.; Bouvy, Nicole; Copaescu, Catalin; de Manzini, Nicolò; Di Lorenzo, Nicola; Morales-Conde, Salvador; Müller, Beat P.; Nickel, Felix; et al. (Surgical endoscopy and other interventional techniques, 2021)
COVID-19 pandemic presented an unexpected challenge for the surgical community in general and Minimally Invasive Surgery (MIS) specialists in particular. This document aims to summarize recent evidence and experts’ opinion and formulate recommendations to guide the surgical community on how to best organize the recovery plan for surgical activity across different sub-specialities after the COVID-19 pandemic.